Percepción de Grupos Relacionados de Diagnóstico y cultura innovadora por profesionales de enfermería (2015)
ABSTRACT: Nursing professionals play an important role at Hospitals when innovation is to be implemented. However, their perception regarding diagnosis related groups as an innovation is unknown. Objective: to characterize how the professionals of a nursing department of a high complexity hospital in Colombia perceive the innovation of diagnosis related groups. Methodology: A case study. Data were collected from surveys and focus groups. Descriptive statistics were calculated for the perception of innovation, and the data from the focus groups were transcribed and analyzed. Results: The perception of the innovative culture was positive and there were differences according to education, hierarchical position and sex; the other variables were not significant. As for the diagnosis related groups as an innovation, only 12.5% of the participants were familiar with them, and their attitude was predominantly positive. The attribute that generated less enthusiasm and greater dispersion, was the complexity of said groups. No differences were observed in the perception of the five attributes for any demographic variable. Conclusions: The homogeneity of perception suggests a favorable environment for implementing the system of diagnosis related groups.